Assessment of multi-stage telescopic control rods in a pebble bed reactor. Part II:corrosion and wear performance - Gabriel Paramucchio; Loïc Durand; Ethan Fowler; Ben Lindley; Adrien Couet (Annals of Nuclear Energy, 2026)

Reproducible benchmark for the SNAP 8 experimental reactor at dry conditions - Samuel Garcia; Isaac Naupa; Oliver Paleen; Ethan Fowler; Anthony Boyd; Dan Kotlyar; Ben Lindley (Annals of Nuclear Energy, 2024)

Evaluating real-world emissions from in-use buses and taxis using on-road remote sensing - Mounisai Siddartha Middela; Srinath Mahesh; Aonghus McNabola; William Smith; David Timoney; Ali Ekhtiari; Ben Fowler; Paul Willis; Rebecca Rose; Jasmine Wareham; Hannah Walker; Bidisha Ghosh (Environmental Pollution, 2024)

On-road remote sensing of vehicles in Dublin: Measurement and emission factor estimation - Srinath Mahesh; Aonghus McNabola; William Smith; David Timoney; Ali Ekhtiari; Ben Fowler; Paul Willis; Rebecca Rose; Jasmine Wareham; Hannah Walker; Bidisha Ghosh (Transportation Research Part D: Transport and Environment, 2023)

Molecular characterization of clinical carbapenem-resistant Enterobacterales from Qatar - Fatma Ben Abid; Clement K. M. Tsui; Yohei Doi; Anand Deshmukh; Christi L. McElheny; William C. Bachman; Erin L. Fowler; Ahmed Albishawi; Kamran Mushtaq; Emad B. Ibrahim; Sanjay H. Doiphode; Manal M. Hamed; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
One hundred forty-nine carbapenem-resistant Enterobacterales from clinical samples obtained between April 2014 and November 2017 were subjected to whole genome sequencing and multi-locus sequence typing. Klebsiella pneumoniae (81, 54.4%) and Escherichia coli (38, 25.5%) were the most common species. Genes encoding metallo-β-lactamases were detected in 68 (45.8%) isolates, and OXA-48-like enzymes in 60 (40.3%). bla NDM-1 (45; 30.2%) and bla OXA-48 (29; 19.5%) were the most frequent. KPC-encoding genes were identified in 5 (3.6%) isolates. Most common sequence types were E. coli ST410 (8; 21.1%) and ST38 (7; 18.4%), and K. pneumoniae ST147 (13; 16%) and ST231 (7; 8.6%).

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

An Analytical Algorithm of Porosity–Permeability for Porous and Fractured Media: Extension to Reactive Transport Conditions and Fitting via Flow-Through Experiments Within Limestone and Dolomite - Selçuk Erol; Sarah Jane Fowler; Mathias Nehler; Eva De Boever; Virginie Harcouët-Menou; Ben Laenen (Transport in Porous Media, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

An Analytical Model of Porosity–Permeability for Porous and Fractured Media - Selçuk Erol; Sarah Jane Fowler; Virginie Harcouët-Menou; Ben Laenen (Transport in Porous Media, 2017)

Cumulative solar irradiance and potential large-scale sea ice algae distribution off East Antarctica (30°E–150°E) - Ben Raymond; K. Meiners; C. W. Fowler; B. Pasquer; G. D. Williams; S. Nicol (Polar Biology, 2009)